The Influence of Experiential Marketing and Influencer Marketing on Purchase Decision of Skintific Skincare Products (Study on Students of UPN “Veteran” East Java at Envio Store Surabaya) - Anggun Fatmawati; Sumainah Fauziah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine and analyze the influence of Experiential Marketing and Influencer Marketing on the purchasing decisions of Skintific skincare products at Envio Store Surabaya. The research employs a quantitative approach with a descriptive quantitative method. The population consists of students from UPN